Training Learning Challenge in the Time of Covid-19 Pandemic in BPSDM of the Province of Papua - Financia Emilia Watungadha (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Covid 19 pandemic appeared in Indonesia around the beginning of 2020. The Covid 19 that attacked Indonesia not only had an impact on health but also on global economic life and education. This study aims to discuss and analyze the learning challenges faced by BPSDM Papua during the Covid 19 pandemic. The research method used is descriptive analysis research, which provides data as accurately as possible about people, the environment or other symptoms, especially to strengthen hypotheses so that they can help strengthen old theories or develop a new theory within the framework. The result of this study is that non-classical/online/e-learning learning during the COVID-19 pandemic is not an excuse for not receiving education, because it is very important for civil servants in every country, namely those in Papua Province to improve their intelligence through education. The benefits provided by the Papua BPSDM organization will apply to each student institution.